The prevalence and use of emerging technologies in STEAM education: A systematic review of the literature - Leavy, Aisling; Dick, Lara; Meletiou‐Mavrotheris, Maria; Paparistodemou, Efi; Stylianou, Elena (Journal of computer assisted learning, 2023)
Background The advent of new and emerging technologies and industries has highlighted the need to equip youth with a unique skillset necessary to cope with a rapidly changing and complex digital era and adapt to modern societies' demands. This need has led to the development of teaching approaches to equip students with creative and innovative skills to help prevent any future skills gap. This shift has fuelled the growth of STEAM (Science, Technology, Engineering, Arts and Mathematics) Education worldwide. Objectives Our goal was to engage in a systematic review of the literature to identify the application and prevalence of emerging technologies within the landscape of STEAM Education. Methods We engaged in a systematic review of the literature. Following the application of exclusion criteria to 461 studies, 43 studies were extracted and analysed. Findings and Conclusions Analysis of these studies provides evidence of the fast‐growing use of innovative emerging technologies within the STEAM landscape across all levels of education, from early childhood to college‐level settings. Our analysis reveals an emphasis on developing STEAM‐related disciplinary knowledge and the desire to develop students' 21st‐century skills with a notable lack of targeted emphasis on developing understandings in the arts disciplines. We identify the need for carefully designed intervention studies involving collaboration between multidisciplinary STEAM experts that use high‐quality measures which support the development of inferences relating to learning outcomes arising from such interventions. Lay Description The need to equip students with creative and innovative skills has fuelled the growth of STEAM (Science, Technology, Engineering, Arts and Mathematics) Education worldwide. Technology can play a vital role in STEAM education, offering boundless capabilities and possibilities for creating high‐quality learning experiences that foster students' innovation creativity, communication and collaboration, critical thinking, and problem‐solving skills. Currently, efforts are made by educational researchers and practitioners worldwide to tap the potential of technology to support STEAM learning environments. A need exists for empirical evidence to support assumptions and hypotheses concerning the role of technology in STEAM education. The article offers a systematic review of the literature to identify the application and prevalence of emerging technologies within the landscape of STEAM Education. The systematic review describes a variety of pioneering STEAM education initiatives that utilize emerging technologies in their designs, but also reveals the challenges and obstacles to integrating STEAM disciplines in a meaningful way.